Assessing the quantity and quality of grassland forage – without labor analysis - Bajnok, Márta; Szentes, Szilárd; Sutyinszky, Zsuzsanna; Tasi, Julianna (Animal welfare, Ethology and Housing Systems (AWETH), 2011)
In practice it is very important to know the quantity and quality of the forage from the grassland and estimate accurately the economic value of the grassland. The goal of this study is to demonstrate a cheap, viable method of estimation the quantity and quality of fodder, the forage and economic value of the grassland. In Hungary Balázs published a three-dimensional method in 1960, which was adaptable for this goal. A group of scientist on the St Stephen University/Szent István university Gödöllő proved this method and corrected, improved it with the help of results of grassland management studies. By the tests the corrected three- dimensional method by Balázs is usable for estimating the yield and assessing the forage value of the grassland (n = 48; r = 0,98; P < 0,05). This method is cheap, needs no equipment. It values the grassland from the needs of animals point of view. Coenological examination of the vegetation and measuring the height of speies is prerequisite. Datas from these field researches are used for compute the yield, the forage value or the economic value. The corrected three-dimensional method by Balázs can be proposed for application.
Keywords: quality of forage; value of the grassland; three-dimensional method